The Effect of Calcination Temperature on the Structural and Magnetic Properties of Co-Precipitated Cofe2o4 Nanoparticles - Casagrande-Denardin, J (Elsevier Ltd, 2017)
Cobalt ferrite (CoFe2O4) nanoparticles were co-precipitated from metal nitrates at the reaction temperatures of 40 and 85 °C for 1 h and were further calcinated at 500 and 800 °C for 2 h. The effect of calcination temperature on the structural, morphological, compositional and magnetic properties was investigated. Both, the reaction and calcination temperatures were significantly influenced the crystallite size and magnetic properties of cobalt ferrite nanoparticles and the crystallite size was increased with the calcination temperature. The synthesized nanoferrites were roughly in spherical morphology with the stoichiometric ratio of 1:2 Co:Fe. Co-precipitated and calcinated cobalt ferrites showed the ferromagnetism at room temperature and 5 K (−268 °C) and the saturation magnetization was increased with the calcination temperature. At low temperature, CoFe2O4 nanoparticles calcinated at 800 °C showed the saturation magnetization of 84.36 and 92.70 emu/g for the reaction temperatures of 40 and 85 °C, respectively and the values were in accordance with the magnetization of bulk cobalt ferrites. © 2017 Elsevier B.V.